2012
DOI: 10.1088/1367-2630/14/7/073052
|View full text |Cite
|
Sign up to set email alerts
|

The electronic phase diagrams of the Eu(Fe0.81Co0.19)2As2superconductor

Abstract: The magnetic and superconducting properties of an Eu(Fe 0.81 Co 0.19 ) 2 As 2 single crystal are investigated by means of ac magnetic susceptibility, dc magnetization, specific heat, transverse resistivity and Hall effect measurements in magnetic fields up to 9 T, applied parallel and perpendicular to the c-axis. The compound exhibits the coexistence of magnetism and superconductivity (SC), characterized by structural distortion (SD) and/or spin-density-wave (SDW) ordering at T SD/SDW = 78 ± 4 K, cantedantifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…1.The SC transition in Co-doped EuFe 2 As 2 is usually more susceptible to the adverse effect of the Eu-magnetic ordering and zero resistivity is only realized within a quite narrow Co-concentration window around 20%. 26 The R-T behavior here is very similar to that reported by Tran et al on a single crystal with a similar composition Eu(Fe 0.81 Co 0.19 ) 2 As 2 , 39 in which also multiple phase transitions with comparable transition temperatures were found.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1.The SC transition in Co-doped EuFe 2 As 2 is usually more susceptible to the adverse effect of the Eu-magnetic ordering and zero resistivity is only realized within a quite narrow Co-concentration window around 20%. 26 The R-T behavior here is very similar to that reported by Tran et al on a single crystal with a similar composition Eu(Fe 0.81 Co 0.19 ) 2 As 2 , 39 in which also multiple phase transitions with comparable transition temperatures were found.…”
Section: Resultssupporting
confidence: 90%
“…(Space group: F mmm) of the Eu 2+ spins is slightly suppressed from T N = 19 K for the parent compound to T C = 17 K with x = 0.18. The c-direction FM ordering of Eu 2+ presented here contrasts with the canted-AFM ordering with an easy a-b plane proposed by Tran et al in a single crystal with similar Co-concentration x = 0.19 based on pure macroscopic measurements 39. The microspopic bulk probe of neutron diffraction in our study, nevertheless, provides convincing evidence for the ferromagnetic ordering of the Eu 2+ moments.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…It was shown that in EuFe 2 As 2 -based systems the saturation state is equivalent to a field-induced ferromagnetic state. 5,11,29,32 The field at which the system "switches" from an antiferromagnetic (AF) to a field-induced ferromagnetic state (FI-FM) is represented by the "crossover" field H cr . Such H cr values can, therefore, be calculated by determining the minimum in the second derivative of magnetization d 2 M /dH 2 .…”
Section: Magnetizationmentioning
confidence: 99%
“…phosphorus, i.e., one has to perturb significantly Fe-As layers with strong perturbation of the iron environment, as iron atoms are tetrahedrally coordinated by pnictogen [10]. It is interesting to note, that 4f antiferromagnetic order occurs within superconducting material as well, and doping leading to superconductivity usually causes some 4f magnetic moment reorientation (canting) with a generation of the 4f ferromagnetic component [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%